Perioperative Complications of Urogynecologic Surgery: Our Experience in a Tertiary Care Hospital - Huseyin Cengiz; Hediye Dagdeviren; Cihan Kaya; Caglar Helvacoglu; Murat Ekin (Medical Network, 2018)
Objective: The aim of this study was to determine the incidence of perioperative complications in women who undergo urogynecologic surgery. Study Design: A retrospective chart review of patients who underwent urogynecologic surgery between January 2014 and January 2016 was performed. The type of surgeries and significant perioperative complications were recorded. Intraoperative complications included, injury of nerves, bowel, bladder or ureter, intraoperative blood transfusion, conversion to laparotomy and anesthesia-related events. Results: The sample included 120 consecutive women who underwent urogynecological surgeries. The mean age of the patients was 53 (range, 34-88 years). 46% of the patients had one or more of medical problems. 55% percent of the patients had previously undergone a pelvic surgery. 70% of the patients had surgeries by vaginal approach, 10% of them had by abdominal approach and 20% of them had surgeries by laparoscopic approach. The prevalence of complications was 27.5%. This included 11 intraoperative complications (6 cases bladder injury, 2 cases transfusion) and 21 postoperative complications. Conclusion: In conclusion, the number of women undergoing surgery for pelvic organ prolapse, urinary incontinence, and anal incontinence continues to increase, the present study provides useful statistical data for our country.